Comunicação terrorista do Estado Islâmico: análise de conteúdo das capas da revista Dabiq (2014-2016) - Santana, Deivid Mota (2024)
The fight against terrorism gained new ramifications with the advent of the internet (Medeiros, 2020). Terrorist groups such as Hamas, Hezbollah, Al-Qaeda and the Islamic State became routinely visible in the media. In this way, the work analyzes the strategies of the Islamic State (IS), specifically, to disseminate terrorist communication through its digital magazine Dabiq (2014-2016). The work is justified due to the need to combat extremism and all forms of violence, hallmarks of terrorism. Furthermore, one of the objectives of the 2030 Agenda is the promotion of peaceful and inclusive societies for development. With this, the dissertation discusses the role of the internet for terrorist organizations, highlighting the use of technology to spread terror. Through a content analysis (Bardin, 2011) of the 15 editions of Dabiq Magazine, the question is: what textual, visual and design resources are used in the content produced? The central objective of the work is to determine which contents are present on the covers of the 15 editions of Dabiq Magazine (2014-2016). It is therefore proposed to present reflections and analyze aspects of magazine covers to quantify their occurrences and uses, considering: topology, typography, eidetic and chromatic qualities and images (Cunha, 2011). From this perspective, the use of sophisticated typography and images on covers tends to show a pseudo-professionalization of terrorist groups in the construction of media content.